2017
DOI: 10.26417/ejser.v11i2.p145-154
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of ICT Use in Teaching in Different Educational Domains

Abstract: This study explored the implementation of the information and communication technology (ICT) into teaching and learning processes in three educational domains (STEM, language education, and other humanities and social sciences). Specificaly, the aim of the current study was to explore the effects of teachers' attitudes towards ICT use in classroom, self-efficacy in the ICT use, and perceived school-level barriers on teachers' ICT use as well as possible domain specific differences in the assessed variables. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
1
4
0
2
Order By: Relevance
“…The study focused on using ICT in teaching science and mathematics in the classroom rather than other subjects because ICT is evidently becoming a necessary tool to enhance the learning of these subjects. A study that compared the use of ICT in various educational domains showed that Science, Technology, Engineering, and Mathematics (STEM) teachers recognize the benefits of using ICT in teaching more than those teaching humanities and social sciences and that they "perceived themselves as more competent in ICT use compared to other two groups" (Zubkovic et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The study focused on using ICT in teaching science and mathematics in the classroom rather than other subjects because ICT is evidently becoming a necessary tool to enhance the learning of these subjects. A study that compared the use of ICT in various educational domains showed that Science, Technology, Engineering, and Mathematics (STEM) teachers recognize the benefits of using ICT in teaching more than those teaching humanities and social sciences and that they "perceived themselves as more competent in ICT use compared to other two groups" (Zubkovic et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the effects of ICT use in education on students were examined from a multidimensional perspective. In the literature, there are many studies on the use of ICT in education (Adam & Metljak, 2022;Guillén-Gámez & Mayorga-Fernández, 2020;Rana, Greenwood & Henderson, 2022;Putri, et al, 2020;Spiteri & Chang Rundgren, 2020;Zubković, Pahljina-Reinić & Kolić-Vehovec, 2022). On the other hand, no study has been found that examines the effects of ICT use in education on primary school students with a mixed method design.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…Notwithstanding, and according to pupils’ views, those teachers who were more inclined and better prepared for pupil-oriented teaching practices – such as group work, individualized learning and project work – are more likely to use digital resources. Several recent studies show that skills in ICT use, self-efficacy and confidence are the most relevant factors to promote the effective use of digital technology by teachers (Hatlevik, 2017; Piedade, 2017; Zubković et al , 2017; Redmond and Lock, 2019). Although digital technology skills and teachers’ attitudes toward the use of technology are considered a central element for the modernization of educational practices, teacher training is not adequate to deal with the challenges faced, particularly concerning the development of innovative pedagogical practices supported by technology.…”
Section: Rationalementioning
confidence: 99%